the second way.
(x+iy)^2 = (x^2 - y^2) + i2xy
NOT
x^2 + (iy)^2
Here's the problem,
(1-i)(1-i)^2 so I worked it like this,
(1-i)(1^2-i^2)=
(1-i)(1-(-1))=
(1-i)(2)=
(2i)
Does that look correct, or should I have started it by working the square in the second set of parentheses like this (1-i)(1-i)(1-i)
??? Surely, you know that (a- b)^2 is NOT a^2- b^2!
(a- b)^2= a^2- 2ab+ b^2. With a= 1, b= i, that is 1- 2(1)(i)+ (i)^2= 1- 2i- 1= -2i
and certainly, (1- i)(2)= 2- 2i not "2i"!(1-i)(1-(-1))=
(1-i)(2)=
(2i)
It's not a matter of where you start, you need to review multiplication of complex numbers completely!Does that look correct, or should I have started it by working the square in the second set of parentheses like this (1-i)(1-i)(1-i)